Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This chapter establishes the Bütschli droplet system as an experimental model to interrogate the technological potential of vibrant matter. The original recipe developed by zoologist Otto Bütschli in 1892 (Bütschli, 1892) was recreated to fully characterize the system. A series of around 300 experiments were conducted in a laboratory setting under the supervision of Associate Professor Martin Hanczyc at the Center for Fundamental Living Technology (FLinT), at the University of Southern Denmark. Each experiment was photographically recorded using a Nikon Eclipse TE2000-S inverted microscope with a Photometrics Cascade II 512 camera and in house software. Having become familiar with the limits and range of the dynamic chemical system, ways to influence its outputs were explored and examined from technical and graphical perspectives. This could be achieved by manipulating internal and external conditions of the system, and suggested that Bütschli droplets could be applied in both technological and drawing contexts. Finally, the ontological and epistemological implications of a non-mechanical40 technology were considered for its potential application within architectural design-led experiments.